Relationship between adverse childhood experiences and illness anxiety in irritable bowel syndrome: the impact of gender - Berens, Sabrina; Banzhaf, Philine; Baumeister, David; Gauss, Annika; Eich, Wolfgang; Schäfert, Rainer; Tesarz, Jonas (Journal of psychosomatic research, 2020)
Objective - Irritable bowel syndrome (IBS) is a functional disorder with a complex biopsychosocial etiopathogenesis. Various psychosocial factors like adverse childhood experiences (ACE) and illness anxiety appear to be relevant, but underlying mechanisms are still not fully understood. Furthermore, there are indicators of gender specific effects of ACE on IBS. Therefore, this study analyzed group differences between IBS patients and healthy controls (HCs) according to ACE and illness anxiety, and the relationship between ACE and illness anxiety by taking gender differences into consideration. - Methods - A cross-sectional multi-center study was conducted comparing IBS patients with HCs. Illness anxiety was recorded using the Whiteley-Index-7, childhood adversities via the 10-item Adverse-Childhood-Experiences-score, anxiety by the Generalized Anxiety Disorder seven-item questionnaire and depressive symptoms using the nine-item depression module of the patient-health-questionnaire. Group differences between IBS patients and HCs were analyzed and correlation analyses were performed. - Results - Overall, 127 gender and education matched participants per group were included. Compared to HCs, IBS patients were characterized by higher prevalences for adverse childhood experiences (63.8% vs. 48.0%, p=.02, OR=1.33) and increased levels of illness anxiety (p<.001, η2=0.595). Taking into account gender specific effects, there was a significant correlation between adverse childhood experiences and illness anxiety in female IBS patients, but not in male (r=0.242, p=.03 vs. r=0.162, p=.29). However, after controlling for depression and anxiety, this correlation disappeared. - Conclusion - Our findings suggest a possible gender-specific association of ACE with illness anxiety in female IBS patients that might be linked to increased levels of depression and anxiety. Trial Registration: DRKS00011685.